Long-term follow-up results of a pilot study for nodular basal cell carcinoma with PDT using partial home treatment protocol - Ana Gabriela Salvio; Mirian D Stringasci; Michelle B Requena; Bianca A. Fregolenti; Maira Monique da Costa Medeiro; Rosilene Guedes Santos; Vanderlei Salvador Bagnato (Photodiagnosis and Photodynamic Therapy)
Significance: Evaluate a photodynamic therapy (PDT) protocol for low-risk basal cell carcinoma (BCC) treatment that requires less time spent at the hospital and is less painful. Approach: Eight BCCs were selected, debulked, and received 20 % methyl aminolevulinate cream. After 3 h, the first irradiation was performed at the hospital (20 min, 150 J/cm2). Then, the cream was re-applied, and a portable irradiation prototype was fixed to the skin around the lesion. After 1.5 h, the patients turned on the prototype for irradiation at home (for 2 h, totalizing 312 J/cm2). Disease-free survival rate and pain score during irradiations were evaluated. Results: The clearance at 30 days after PDT was 87.5 % by histological analysis. The mean follow-up was 21.5 months and the recurrence-free survival at 22 months was 75 %. The pain score was significantly lower at home. Conclusions: A potentially less painful and more comfortable PDT treatment protocol with proven long-term efficiency is presented. A randomized clinical trial has been conducted to confirm these results.